Improved Processing of Carbon Nanotube Yarn. (3rd April 2013) - Jayasinghe, Chaminda; Amstutz, Trent; Schulz, Mark J.; Shanov, Vesselin
Abstract : We compared mechanical and electrical properties of carbon nanotube (CNT) yarns formed from four different spinning methods. In these methods, a yarn was spun from two aligned CNT arrays. CNT yarns fabricated from each method were tested quantitatively through the mechanical and electrical properties and reported. This improvement is considered to be caused by multiple factors, such as reduction of the yarn diameter, densification, water evaporation, and CNT orientation. The best electrical and mechanical property of CNT yarn was observed from the fourth spinning method where heating and tension during spinning were applied. The introduced yarn spinning methods are appropriate for continuous mass production of high strength carbon nanotube yarns with controlled diameter, strength, and electrical conductivity.